Detection of Fungi Contaminated some Nuts and Its Ability for Aflatoxin B1 Production. Issue 1 (1st July 2022) - Al-Warshan, Salim H.S.; Abed, Mohammed Majid; Mohammed, Mustafa M.
Abstract: This study was conducted in February and March 2021 to collect data on the incidence of aflatoxinB1 (AFB1) and the ability of fungi isolated from nuts (almond, pistachio, hazelnut, cashew, imported and local peanut) to produce AFB1 in Ramadi city, Iraq. The mycological investigation revealed the isolation of fourteen fungal species from eight genera, Aspergillus flavus was the most common and widely distributed fungus. TLC analysis was used to assess Aspergillus flavus' ability to produce aflatoxinB1. The majority of A.flavus isolates In the culture media(YES) were toxigenic and capable of producing aflatoxinB1. The ability to produce aflatoxin B1 ranged from 30 - 40, 25 – 60, 15 – 50, 20 – 20, 40 – 70, 65 – 150 ppb in almond, pistachio, hazelnut, cashew, imported and local peanut respectively. The ELISA approach was used to estimate the natural occurrence of AflatoxinB1 in nuts samples. Contaminated samples with aflatoxinB1 were 40, 20, 40, 40, 80 and 80 % of tested samples for almond, pistachio, hazelnut, cashew, imported and local peanut, Concentrations of aflatoxin B1 were ranged between 9 – 16, 17 – 45, 20 – 26, 10 – 12, 180 – 190, 150 – 225 ppb respectively. The results show that most samples have a high contamination of AlatoxinB1 that is higher than health standards for consumption (20ppb). Mycotoxigenic A. flavus isolates are high contaminants for food and should be removed to reduce the risk of nut toxin contamination.